Promoting Railway Safety Awareness for Early Childhood Learners Through Community-Based Socialization in Madiun - Damar Isti Pratiwi; Windi Nopriyanto; Teguh Arifianto; Nanda Ahda Imron (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
This community service activity was conducted to improve early childhood learners’ railway safety awareness in Madiun City, where children are frequently exposed to railway environments but have limited understanding of railway safety practices. The activity aimed to introduce age-appropriate railway safety education through community-based socialization conducted at Politeknik Perkeretaapian Indonesia (PPI) Madiun. The participants consisted of 120 early childhood learners, 12 teachers, and 70 parents from several early childhood education institutions in Madiun. The activity was implemented through four stages: preliminary preparation and needs assessment, digital dissemination through WhatsApp and Instagram, experiential learning-based socialization, and reflection and evaluation. Learning activities included storytelling, animated educational videos, interactive discussions, role-play simulations, and demonstrations using miniature railway models. Data were collected using observation sheets, field notes, oral questioning, and feedback questionnaires from teachers and parents. The findings showed measurable improvements in children’s railway safety awareness after the activity. Understanding of railway warning symbols increased from 28% to 87%, awareness of safe behavior near railway tracks increased from 35% to 89%, and the ability to repeat key railway safety messages increased from 22% to 81%. Teachers and parents also reported positive evaluations regarding the relevance and effectiveness of the learning materials. These findings indicate that experiential and participatory learning approaches conducted in a vocational railway environment effectively improve railway safety awareness among early childhood learners and provide a replicable model for community-based railway safety education.